Better water jump clearances were differentiated by longer landing distances in the 2017 IAAF World Championship 3000 m steeplechase finals. Issue 3 (1st February 2020) - Hanley, Brian; Bissas, Athanassios; Merlino, Stéphane
ABSTRACT: The aim of this novel study was to analyse key kinematic variables during the water jump clearance amongst world-class 3, 000 m steeplechasers. Thirteen men and 13 women were recorded as they negotiated the last water jump in the 2017 IAAF World Championship finals. Video footage (100 Hz) was recorded using three high-definition camcorders to derive spatiotemporal data; spatial data were normalised to athletes' statures. The time to cover the distance from 4.5 m before the water jump barrier to 4.5 m after ("9 m time") was used to describe overall clearance success. Although men had longer approach and exit step lengths, there were no differences when the data were normalised; by contrast, men's landing distances were greater in both absolute and relative terms. Women's shorter landing distances meant negotiating deeper water when exiting, with those athletes with longer landing distances running faster 9 m times ( r = – 0.87). Obtaining a high position on the barrier (clearance height) was correlated with longer landing distances (men: r = 0.75, women: r = 0.71) and could indicate better technique. Coaches should note that although technical proficiency in all aspects of the clearance is imperative, optimising the athlete's landing distance is paramount.